AN ANALYSIS OF AN EAP COURSE BOOK USED IN ISLAMIC HIGHER EDUCATION - Fikry Fikry (UAD TEFL International Conference)
Selecting EAP Course book which is suitable for Islamic Studies students is not an easy job to handle. To know the strengths and weaknesses of the course book, there should be an evaluation.   This study evaluates English Textbook, Islamic Learning in EAP which is designed for undergraduate students learning Islamic Studies at Islamic Higher Education. Two points were addressed in this study: (1) has the content of textbook meet the criteria of Language teaching principles? (2) has the textbook followed proper EAP materials and tasks?This is a qualitative research with content analysis method. The data was the textbook of Islamic Learning in EAP by Ahwy Oktradiksa (2013). The content of course book was analyzed based on principles of language teaching by Paul Nation (2010) and design of EAP materials and tasks by Stoller (2016). The findings reveal the strengths and weaknesses of Islamic Learning in EAP. This study indicates that (1) the course book has poor quality and has not met the criteria of language teaching principles covering: (a) content and sequencing, (b) format and presentation, (c) monitoring and assessment; (2) the course book does not cover the content of EAP materials and tasks. It tends to present general English and does not stimulate to develop language and academic skills, critical thinking skills, introduce technology into learning activities and do not provide with some strategies to English test skills like TOEFL or IELTS. This study will contribute significantly to curriculum and materials developers, teachers, and students interested in EFL learning.